Incorporating Diversity and Inclusion in Early Childhood Education - Kâmil Khaskheli (Journal of Education Review Provision, 2021)
The purpose of this research was to learn more about the variables that affect teachers' perspectives on diversity and inclusion in the classroom. Two hundred early childhood instructors were surveyed, and twenty were interviewed further as part of a quantitative study strategy. Methods such as descriptive statistics, analysis of variance analyses, and regression analysis were used to examine the data. The findings imply that teachers are aware of and open to taking action in support of efforts to increase school variety and inclusion. However, socioeconomic variables like education level and years of experience may lead to variations in perspectives on diversity and inclusion. Instructors with more training and experience were more likely to consider diversity and inclusion crucial, and they also had greater faith in their own abilities to foster such values. The results stress the importance of teachers and the need for continuing efforts to support their professional growth and training in fostering an environment that values and celebrates differences among children in pre-school and kindergarten. Last but not least, ensuring that all children are given a fair chance to flourish in life requires a commitment to variety and equality in early childhood education.